Improved LEACH Routing Communication Protocol for Wireless Sensor Network (International Journal of Engineering and Computer Science, 2016)
WSN (wireless sensor network) consists of thousands of sensor nodes which have limited energy, memory, and computation capability. In some of extreme environment, it becomes difficult to replace the sensor nodes once they used up the resources. Therefore, many researchers in this field focus on how to design an efficient routing protocol to prolong the life span of the network. The hierarchical protocols such as LEACH and LEACH-C have better performance in saving the energy consumption. However, neglecting the choosing formula of CHs and non-CHs makes the consumption of too much energysH. In order to reduce the energy consumption, we improve the tradition method used for selecting cluster heads. Meanwhile, we establish a vice cluster head for each cluster to reduce the energy consumption and prolong the lifetime. Hence, simulations show that our improved protocol performs better than the LEACH and the LEACH-C.